2019
DOI: 10.21608/edj.2019.71241
|View full text |Cite
|
Sign up to set email alerts
|

Clinical And Radiographic Evaluation Of Biodentine Versus Formocresol In Vital Pulpotomy Of Primary Molars (A Randomized Control Clinical Trial)

Abstract: Background:The main objective of pulp therapy is to preserve the integrity and health of the teeth and their supporting tissues, as well as to maintain the pulp vitality. Formocresol (FC) is that fixing agent which is considered as gold standard and used as pulpotomy medicament for primary teeth for decades. Several concerns had been reported about the use of FC. These concerns push new medicaments to be used for pulpotomy purposes. Among these medicaments is Biodentine (BD). Aim of the study:To compare FC and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…After 12 months follow-up period, formocresol group showed clinical success rates of 89.5%, 94.7% and 89.5% by evaluation of teeth mobility, fistulous tract formation and pain with percussion, respectively. These findings are consistent with those of Elbardissy & El-Sayed (42) study in which biodentine showed 100% clinical success at all follow up periods, however FC showed 95.1% clinical success. This may attributed to the fact that the fixation of pulp tissue using FC is never complete.…”
Section: Discussionsupporting
confidence: 92%
“…After 12 months follow-up period, formocresol group showed clinical success rates of 89.5%, 94.7% and 89.5% by evaluation of teeth mobility, fistulous tract formation and pain with percussion, respectively. These findings are consistent with those of Elbardissy & El-Sayed (42) study in which biodentine showed 100% clinical success at all follow up periods, however FC showed 95.1% clinical success. This may attributed to the fact that the fixation of pulp tissue using FC is never complete.…”
Section: Discussionsupporting
confidence: 92%
“…Four to seven years old children were involved in this study as they are more cooperative with easier behaviour management (22) ; this age is suitable for treating primary molars as it is away from the age of physiological resorption. The teeth used in this study and the treatment were chosen based on the AAPD guidelines for pulp therapy in primary and immature permanent teeth (23) .…”
Section: Success Ratementioning
confidence: 99%